The Implementation of Holistic Learning in Modern Education Context Based on Propethic Hadith - Mukhtaroh, Ita; Muhid, Muhid (Yayasan Rahmat Islamiyah, 2025)
Modern education often prioritizes cognitive achievement yet neglecting spiritual, moral, and emotional development. This article aims to analyze the application of holistic learning principles derived from the Prophetic hadith and their relevance to contemporary educational challenges. Employing a descriptive qualitative method with a library research approach, the study examines selected tarbawi hadiths alongside supporting literature. The findings reveal that the Prophet’s teachings emphasize character formation, spiritual growth, and a balance between intellectual and moral dimensions. These principles are universal and remain contextually relevant across time, providing a strong foundation for developing an Islamic holistic education model. In conclusion, integrating hadith-based values into modern educational systems can nurture learners who are not only intellectually competent but also morally upright, spiritually mature, and socially responsible.